Disease status, reasons for discontinuation and adverse events in 1038 Italian children with juvenile idiopathic arthritis treated with etanercept. Issue 1 (December 2016) - Verazza, Sara; Davì, Sergio; Consolaro, Alessandro; Bovis, Francesca; Insalaco, Antonella; Magni-Manzoni, Silvia; Nicolai, Rebecca; Marafon, Denise; De Benedetti, Fabrizio; Gerloni, Valeria; Pontikaki, Irene; Rovelli, Francesca; et al.
Abstract Background Data from routine clinical practice are needed to further define the efficacy and safety of biologic medications in children with juvenile idiopathic arthritis (JIA). The aim of this analysis was to investigate the disease status, reasons for discontinuation and adverse events in Italian JIA patients treated with etanercept (ETN). Methods In 2013, all centers of the Italian Pediatric Rheumatology Study Group were asked to make a census of patients given ETN after January 2000. Patients were classified in three groups: group 1 = patients still taking ETN; group 2 = patients discontinued from ETN for any reasons; group 3 = patients lost to follow-up while receiving ETN. All three groups received a retrospective assessment; patients in group 1 also underwent a cross-sectional assessment. Results 1038 patients were enrolled by 23 centers: 422 (40.7%) were in group 1, 462 (44.5%) in group 2, and 154 (14.8%) in group 3. Median duration of ETN therapy was 2.5 years. At cross-sectional assessment, 41.8% to 48.6% of patients in group 1 met formal criteria for inactive disease, whereas 52.4% of patients in group 2 and 55.8% of patients in group 3 were judged in clinical remission by their caring physician at last visit. A relatively greater proportion of patients with systemic arthritis were discontinued or lost to follow-up. Parent evaluations at cross-sectional visit in group 1 showed that 52.4% of patients had normal physical function, very few had impairment in quality of life, 51.2% had no pain, 76% had no morning stiffness, and 82.7% of parents were satisfied with their child's illness outcome. Clinically significant adverse events were reported for 27.8% of patients and ETN was discontinued for side effects in 9.5%. The most common adverse events were new onset or recurrent uveitis (10.2%), infections (6.6%), injection site reactions (4.4%), and neuropsychiatric (3.1%), gastrointestinal (2.4%), and hematological disorders (2.1%). Ten patients developed an inflammatory bowel disease and 2 had a malignancy. One patient died of a fulminant streptococcal sepsis. Conclusions Around half of the patients achieved complete disease quiescence under treatment with ETN. The medication was overall well tolerated, as only one quarter of patients experienced clinically significant adverse events and less than 10% had treatment discontinued for toxicity.